2016
DOI: 10.1002/pbc.25958
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Adds Prognostic Value to Minimal Residual Disease Status in Pediatric T‐Cell Acute Lymphoblastic Leukemia

Abstract: Background Despite increased knowledge about genetic aberrations in pediatric T‐cell acute lymphoblastic leukemia (T‐ALL), no clinically feasible treatment‐stratifying marker exists at diagnosis. Instead patients are enrolled in intensive induction therapies with substantial side effects. In modern protocols, therapy response is monitored by minimal residual disease (MRD) analysis and used for postinduction risk group stratification. DNA methylation profiling is a candidate for subtype discrimination at diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
62
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(68 citation statements)
references
References 38 publications
(97 reference statements)
6
62
0
Order By: Relevance
“…This has, however, not been seen in all studies and, furthermore, these studies were based on quite a low number of patients, which often included both pediatric and adult patients, precluding any firm conclusions as to the prognostic role of miRs in childhood T‐ALL (Kaddar et al, ; Gimenes‐Teixeira et al, ; Xi et al, ). Data on promoters that are differentially methylated in T‐ALL have been applied to define CpG island methylator phenotypes, delineating cases as either hypermethylated or hypomethylated (Borssén et al, ), with hypomethylated cases having a significantly worse event‐free and overall survival in one of the studies (Borssén et al, ). Obviously, this needs to be addressed in larger, prospective cohorts.…”
Section: Clinical Genetic and Epigenetic Features And Prognosismentioning
confidence: 99%
“…This has, however, not been seen in all studies and, furthermore, these studies were based on quite a low number of patients, which often included both pediatric and adult patients, precluding any firm conclusions as to the prognostic role of miRs in childhood T‐ALL (Kaddar et al, ; Gimenes‐Teixeira et al, ; Xi et al, ). Data on promoters that are differentially methylated in T‐ALL have been applied to define CpG island methylator phenotypes, delineating cases as either hypermethylated or hypomethylated (Borssén et al, ), with hypomethylated cases having a significantly worse event‐free and overall survival in one of the studies (Borssén et al, ). Obviously, this needs to be addressed in larger, prospective cohorts.…”
Section: Clinical Genetic and Epigenetic Features And Prognosismentioning
confidence: 99%
“…DNA methylation alterations have been associated with prognosis in various hematological disorders . We have previously shown, in two independent cohorts, prognostically relevant subgrouping of pediatric T‐ALL samples at diagnosis based on a CIMP (CpG island methylator phenotype) panel including 1293 gene promoter enriched CpG sites . In both cohorts, the CIMP− subgroup, with a methylation profile closer to normal T cells, had a worse prognosis than the CIMP+ subgroup (36% vs 86% 5‐year event‐free survival in the NOPHO ALL 1992/2000 treated cohort and 29% vs 6% 3‐year cumulative incidence of relapse in the NOPHO ALL 2008 treated cohort) .…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown, in two independent cohorts, prognostically relevant subgrouping of pediatric T‐ALL samples at diagnosis based on a CIMP (CpG island methylator phenotype) panel including 1293 gene promoter enriched CpG sites . In both cohorts, the CIMP− subgroup, with a methylation profile closer to normal T cells, had a worse prognosis than the CIMP+ subgroup (36% vs 86% 5‐year event‐free survival in the NOPHO ALL 1992/2000 treated cohort and 29% vs 6% 3‐year cumulative incidence of relapse in the NOPHO ALL 2008 treated cohort) . The prognostic relevance was further strengthened in the NOPHO ALL 2008 treated cohort by combining CIMP status with minimal residual disease (MRD) status at the end of the induction therapy, which allowed subgrouping of high‐risk T‐ALL patients (MRD > 0.1% at day 29) (3‐year cumulative incidence of relapse in the MRD > 0.1%/CIMP− subgroup was 50% vs 12% in the MRD>0.1%/CIMP+ subgroup) …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, various studies have shown an important role of epigenetic aberrations in the pathogenesis of pediatric acute leukemia, including T-ALL, and resistance to chemotherapy [6]. In particular, Borssen et al recently showed that the amount of CpG island methylation could predict the outcome and response to standard treatment [7]. …”
Section: Introductionmentioning
confidence: 99%